2019
DOI: 10.1128/aac.01530-18
|View full text |Cite
|
Sign up to set email alerts
|

Pathway-Directed Screen for Inhibitors of the Bacterial Cell Elongation Machinery

Abstract: New antibiotics are needed to combat the growing problem of resistant bacterial infections. An attractive avenue toward the discovery of such next-generation therapies is to identify novel inhibitors of clinically validated targets, like cell wall biogenesis. We have therefore developed a pathway-directed whole-cell screen for small molecules that block the activity of the Rod system of Escherichia coli. This conserved multiprotein complex is required for cell elongation and the morphogenesis of rod-shaped bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 51 publications
(90 reference statements)
2
19
0
Order By: Relevance
“…MAC13243 and A22 were suggested to act on LolA to permeabilize the OM. However, recent work from the Bernhardt group proposed an alternate explanation that could account for the resistance against A22, MAC13243, and related compounds conferred by LolA overproduction [132]. When LolA is produced in excess, the Rcs cell envelope stress response is activated, and LolA overproduction is only protective against the compounds when the Rcs response is intact.…”
Section: Inhibiting Lipoprotein Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…MAC13243 and A22 were suggested to act on LolA to permeabilize the OM. However, recent work from the Bernhardt group proposed an alternate explanation that could account for the resistance against A22, MAC13243, and related compounds conferred by LolA overproduction [132]. When LolA is produced in excess, the Rcs cell envelope stress response is activated, and LolA overproduction is only protective against the compounds when the Rcs response is intact.…”
Section: Inhibiting Lipoprotein Transportmentioning
confidence: 99%
“…When LolA is produced in excess, the Rcs cell envelope stress response is activated, and LolA overproduction is only protective against the compounds when the Rcs response is intact. The Bernhardt group illustrated that inactivating RcsB, the transcriptional regulator of the Rcs system, abrogates the protective effect of LolA overproduction [132]. LolA and LolB are also potentially interesting targets for novel therapeutics.…”
Section: Inhibiting Lipoprotein Transportmentioning
confidence: 99%
“…It is believed that CBR-4830 inhibits MreB by competing with ATP for binding to the nucleotide binding pocket (Robertson et al, 2007). It has also been reported that CBR-4830 inhibits the growth of wild-type E. coli and induces spherical cells but may have significant off-target activity (Buss et al, 2019). Sceptrin ( Figure 2G) is a natural product isolated from a marine sponge, Agelas confera (Walker et al, 1981;Cipres et al, 2010), and seems to have affinity for MreB (Rodríguez et al, 2008).…”
Section: Other Inhibitorsmentioning
confidence: 99%
“…Like MAC13234, compound A is also believed to target MreB in the A22-like fashion by hydrolyzing to produce MP265. A more recent study (Buss et al, 2019) adopted a pathwaydirected whole-cell screening technique to identify compounds 1 and 4 ( Figures 2D,E) as active against E. coli by targeting MreB. Compounds 1 and 4 are also believed to inhibit MreB by hydrolyzing to produce A22 analogs.…”
Section: A22 and Its Analogsmentioning
confidence: 99%
“…In addition, whole cell screens for growth inhibition typically generate large numbers of active compounds, many of which have non-specific activities (Silver, 2011). Therefore, including a counter-screen that facilitates exclusion of non-specific inhibitors and allows identification of compounds targeting specific pathways early in the screening workflow can speed up the screening process tremendously (French et al, 2017;Buss et al, 2018).…”
Section: Introductionmentioning
confidence: 99%